Analysing the Arab-Israeli identity crisis in the author Sayed Kashua’s Dancing Arabs and Let It Be Morning - Rowshan, Faria (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Master of Arts in English, 2018.